Attitudinal factors affecting wiki group collaboration for English writing - Chen, Chwen Jen; Chuah, Kee-Man; Tho, Jimmy; Teh, Chee Siong (European Journal of Open, Distance and E-learning, 2015)
Wikis, being one of the popular Web 2.0 tools, have impacted students’ engagement and performance particularly in the aspects of second and foreign language learning. While an increasing number of studies have focused on the effectiveness of wiki in improving students’ writing skills, this study was conducted to examine the attitudinal factors that influence English as a Second Language (ESL) students’ group collaboration in using wikis for a writing task that was divided into three phases: pre-writing, individual-construction, joint-constructions. Data collected from these students after completing this task was analyzed based on three attitudinal aspects: motivation, perceived usefulness, and perceived ease of use. The findings reveal high mean scores for all aspects. Further multiple regression analysis reveals that motivation is the most important factor associated with group collaboration, indicating the need to boost students’ motivation to encourage effective collaboration in completing wiki writing tasks.